The Effect of Hygiene and Motivator Factors on Employee Retention. A Case Study in Padiberas Nasional Berhad (BERNAS) Kelantan - Nur Fauzan, Fauzi (2012)
The objective of this study was to examine the relationship between for factors which are work environment,compensation, training/development and supervisor support and employee retention in Padi Beras Nasional Berhad (BERNAS) in Kelantan. The research done by mean of survey, a questionnaire was distributed to 60 respondents. Data was analyzed by “Statistical Package for Social Science”(SPSS Window) Version 16.0. Correlation analysis was used to test the inter correlation between the variables. Correlation result shows that two variables i.e work environment and supervisor support were correlated and two variables i.e compensation and training/development were not correlated with employee retention in the organization. However,in the multiple regression analysis, it was found that work environment, compensation, training/development and supervisor support were related to employee retention. Work environment has the higher effect on employee retention. This means that work environment is the dominant factor influencing the employee retention of the BERNAS Kelantan workers. These findings show that the related factors should be given attention to retain employees in the organization. Some recommendation have been offered for the organization and future research.